1991
DOI: 10.1016/0892-0354(91)90017-7
|View full text |Cite
|
Sign up to set email alerts
|

Localization of nucleolar chromatin by immunocytochemistry and in situ hybridization at the electron microscopic level

Abstract: Abstract-Nucleoli are the morphological expression of the activity of a defined set of chromosomal segments bearing rRNA genes. The topological distribution and composition of the intranucleolar chromatin as well as the definition of nucleolar structures in which enzymes of the rDNA transcription machinery reside have been investigated in mammalian cells by various immunogold labelling approaches at the ultrastructural level. The precise intranucleolar location of rRNA genes has been further specified by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 96 publications
(102 reference statements)
1
26
0
Order By: Relevance
“…1995). Thus, UBF was revealed predominantly in the dense fibrillar component (DFC) (Roussel et al, 1993), at the periphery of fibrillar centers (FC) (Zatsepina et al, 1993), or in both the DFC and FC Rodrigo et al, 1992;Raska et al, 1995), as well as rDNA (Thiry et al, 1990;Wachtlcret al, 1992;Jimcncz-Garcia et al, 1993).…”
Section: Ubf and Rdna At Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…1995). Thus, UBF was revealed predominantly in the dense fibrillar component (DFC) (Roussel et al, 1993), at the periphery of fibrillar centers (FC) (Zatsepina et al, 1993), or in both the DFC and FC Rodrigo et al, 1992;Raska et al, 1995), as well as rDNA (Thiry et al, 1990;Wachtlcret al, 1992;Jimcncz-Garcia et al, 1993).…”
Section: Ubf and Rdna At Mitosismentioning
confidence: 99%
“…in situ hybridization with specific rRNA or rDNA probes has been developed (Evans et al. 1974;Wachtler et al, 1986;Thiry et al. 1990).…”
mentioning
confidence: 99%
“…These include autoradiography of cells pulse-labelled with tritiated uridine, selective DNA staining, in situ hybridization with appropriate rDNA probes, immunolocalization of intranucleolar DNA by using antibodies directed against DNA, and immunogold detection of enzymes involved in rDNA transcription such as RNA polymerase I and DNA topoisomerase I (summarized in Scheer and Benavente 1990;Derenzini et al 1990;Thiry et al 1991). These studies have clearly shown that the fibrillar centers are the sole nucleolar elements where rDNA as well as the transcriptional machinery coexist.…”
Section: Molecular Architecture Of the Nucleolusmentioning
confidence: 99%
“…Although several nucleolar proteins are known to be targeted to restricted domains within the nucleolus, there is a discrepancy concerning the spatial distribution of ribosomal DNA (rDNA) in these domains. In nucleoli of animal cells, rDNA is suggested to reside in the DFC (Wachtler et al 1990) or in the FC (Thiry et al 1991). On the other hand, in nucleoli of higher plant cells, it is likely that rDNA is mostly localized to the FC (Martin et al 1989;Shaw 1990, Sato andYano 1994).…”
Section: Introductionmentioning
confidence: 97%